Cross-cultural adaptation and psychometric properties of the Indonesian version of the social entrepreneurial antecedents scale in college student - Reny Yuniasanti; Martaria Rizky Rinaldi; Sowanya Ardi Prahara; Nina Fitriana (Insight: Jurnal Ilmiah Psikologi, 2024)
The concept of social entrepreneurship has gained popularity in Indonesia. However, there has been a lack of development in measuring individuals' readiness or interest in social entrepreneurship within the Indonesian context. Based on a literature review, there are no existing studies that have translated and adapted instruments to measure the antecedents of social entrepreneurship for students. One such instrument, the Social Entrepreneurial Antecedents Scale (SEAS), was originally developed to assess social entrepreneurial intentions. This study aims to adapt the scale, especially for students in tertiary institutions for 131 students. Following Beaton's theoretical framework, the research was conducted in six stages: translation, synthesis, back translation, expert committee review, pre-testing, and assessment. The construct validity of the adapted scale was analyzed through confirmatory factor analysis using JAMOVI, focusing on four aspects of social entrepreneurship: empathy, moral obligation, self-efficacy, and social support. The adapted scale, which consists of 14 items, has a reliability coefficient of 0.835. Item discrimination for these 14 items ranged from 0.207 to 0.684. Based on the adaptation process results, this sociopreneurship scale is valid for measuring social entrepreneurial intentions and evaluating the effectiveness of interventions aimed at fostering such intentions. Keyword: Scale adaptation; social entrepreneurship; sociopreneur; students.